2008
DOI: 10.1002/ccd.21640
|View full text |Cite
|
Sign up to set email alerts
|

Initial results of primary device closure of large muscular ventricular septal defects in early infancy using perventricular access

Abstract: Objectives: To report our experience with the use of the Amplatzer muscular ventricular septal defect (VSD) occluder, using direct right ventricle free wall puncture for primary closure of muscular VSDs in infants. Background: Young infants with heart failure due to large or multiple muscular VSDs often require intervention at a stage when percutaneous device closure is impractical due to delivery system limitations. There are considerable benefits to avoiding bypass in these infants. Methods: Patients with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0
5

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 14 publications
3
86
0
5
Order By: Relevance
“…Crossland et al confirmed that perventricular device closure of isolated large mVSD is safe and effective in 8 infants (median age e 14 (2e41) weeks; median weight e 4 (3e6.6) kg) at short-term followup. 13 Gan et al reported similar results in 8 patients (mean age 2.5 AE 3.6 years, mean weight of 10.9 AE 7.6 kg) with postprocedural hospital stay of 7.9 AE 2.2 days. 14 In their experience on mVSD device closure, Karim et al undertook successful perventricular device closure in 8 out of 20 infants.…”
Section: Discussionsupporting
confidence: 64%
“…Crossland et al confirmed that perventricular device closure of isolated large mVSD is safe and effective in 8 infants (median age e 14 (2e41) weeks; median weight e 4 (3e6.6) kg) at short-term followup. 13 Gan et al reported similar results in 8 patients (mean age 2.5 AE 3.6 years, mean weight of 10.9 AE 7.6 kg) with postprocedural hospital stay of 7.9 AE 2.2 days. 14 In their experience on mVSD device closure, Karim et al undertook successful perventricular device closure in 8 out of 20 infants.…”
Section: Discussionsupporting
confidence: 64%
“…Coexistence of congenital heart defects and additional muscular septal defects leading to oversized systemic-to-pulmonary blood flow increases the risk of pulmonary hypertension and heart failure [4]. In this specific group the decision of challenging surgical correction is questionable with regard to morphology of basic defects, patients' weight and age, as well as additional problems.…”
Section: Discussionmentioning
confidence: 99%
“…Different hybrid approaches have been reported in small groups, but there are several limitations of hybrid procedures in borderline children that are related to technological development of miniaturized implants and delivery systems [4]. After a hybrid approach with artificial elements implanted on the beating heart, heparin is recommended in the early postoperative period, with antiplatelet agents finally administered orally.…”
Section: Discussionmentioning
confidence: 99%
“…The avoidance of open-heart surgery in infants has been investigated with some success by other groups [10,11,12,13]. Since 2010, we have treated infants with large muscular VSDs measuring between 7 and 15 mm via transthoracic closure without cardiopulmonary bypass with good outcomes.…”
Section: Introductionmentioning
confidence: 92%